Invitro Alpha Amylase Inhibitory and Anti- Inflammatory Activity of the Leaves Extract Of Denseflower Knotweed (Persicaria Glabra): Inhibitory effects of Persicaria glabra on α-amylase and anti-inflammatory activity - Rahman, M M; Moni, Z R; Rahman, M M (Bangladesh Journal of Agriculture, 2025)
The primary objective of this study was to examine the inhibitory effects of Persicaria glabra on α-amylase and its potential anti-inflammatory properties. (Mention the period and location of experiment, and sources of variation i.e. treatment, replication etc.).The α-amylase inhibitory activity of leaves extracts from P. glabra was assessed using the 3,5-dinitrosalicylic acid (DNSA) methodology, while the anti-inflammatory activities were evaluated using the egg albumin denaturation method. The methanolic and aqueous extract of P. glabra exhibited strong inhibitory activity against α-amylase and demonstrated anti-inflammatory properties. The methanolic extract exhibited an IC50 value of 5.43 mg/mL for α-amylase inhibitory activity, while the aqueous extract had an IC50 value of 6.01 mg/mL. In terms of anti-inflammatory activity, the IC50 values for the methanolic and aqueous extracts were 128.04 µg/mL and 95.96 µg/mL, respectively. The phytochemicals have been found in P. glabra that demonstrated strong inhibition of α-amylase and possess anti-inflammatory properties, which could have significant implications in the fields of medical and veterinary science. Bangladesh J. Agri. 2025, 50(1): 64-71